Augmented Reality for the Architectural Layout of Pura Luhur Candi Narmada Tanah Kilap - Made Suci Ariantini; I Dewa Gde Agung Krisna Dharma Prabhawa; Ketut Sepdyana Kartini; I Putu Gede Abdi Sudiatmika (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2026)
By using Augmented Reality (AR) technology to introduce Pelinggih (shrines), this study seeks to aid Pura Luhur Candi Narmada Tanah Kilap's cultural digitization process. Through an interactive and visual approach, this technology offers the community and visitors a unique way to learn about the shrine's construction history. Through the use of markers inserted in a specially created AR Book, the AR implementation employs the Marker Based Tracking technique. This AR book allows users to examine 3D models of each shrine, complete with audio explanations, bilingual descriptions (in English and Indonesian), and interactive capabilities like object rotation and zooming. This invention provides a cutting-edge and instructive substitute for promoting cultural heritage. Software engineering is used in the development of the AR application. 20 respondents participated in a usability assessment using the System Usability Scale (SUS) approach. With an average score of 82.2%, which is classified as